TECHNOLOGICAL PROCESS OF USING CHEMICAL YARN TO INCREASE THE SOFTNESS OF FLUFFY FABRICS - Doniyorov Bektosh Bahodirovich,; Razzakov Jafar Abduvali o’g’li, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Anntotion: This article presents the types of fluff fabrics, the sequence of technological processes in production, areas of use, and the technological processes of using water-soluble chemical yarn to increase the fluffiness and hygroscopicity of fluff fabrics. It also provides information on obtaining new possibilities in fabrics based on mixing the chemical yarn minwal yarn used in the production of fluff fabrics with cotton fiber yarn, the process of obtaining mixed yarn, test experiments carried out on the resulting fabrics, and conclusions and suggestions based on the results of the experiment.